Educar, divulgar, persuadir: propostas e ações da Diretoria de Higiene de Minas Gerais (1910-1927) - Liliane Tiburcio de Oliveira (2014)
This study discusses the activities of the Diretoria de Higiene de Minas Gerais, responsible for State health service, in the years 1910 to 1927. The main objective was to understand the educational dimension of proposals and actions aimed at spreading hygiene notions among the population. For this purpose, it sought to seize the education conception of the people who worked in the division, mostly doctors. In this way, the work aims to contribute with the historiographical production of the field of education history, especially in relation to the dialogue established between education, hygiene and public health in the 1910s and 1920s, in Brazil. The proposed timeframe covers the operation period of the division during the 20th century. Firstly organized in 1895, it had its activities concluded in 1898. With the reorganization of the state health service, by Decree 2733 of January 11st 1910, the Diretoria de Higiene was anew created and it acted until 1927, when it was established the Diretoria de Saúde Pública. In order to assemble a narrative about the Diretoria de Higiene, were consulted the state Public File documents, as the reports of the division, the mail exchanged between the division and the Secretaria do Interior and the enrolment record book of the officials. In the Legislative Assembly of Minas Gerais, reports of the Presidents of Minas Gerais State were consulted, as well as decrees and laws pertaining to the health service at that period were also taken as sources in this work. By reading and analyzing all this documentary corpus it was possible to understand the modes of action of Diretoria de Higiene and the goals that guidethese actions. Until 1917, the departament prioritized the services performed in the Capital that comprised the diseases notification, health surveillance, isolation, vaccination and disinfection. The interventions in other cities just occurred in epidemics times. From 1918 onward, great emphasis was given to rural sanitation, which resulted in widening of the activities in the State. The contracts signed with the Federal Government and also with the Rockefeller Foundation were important for the consolidation of the new purpose. With this objective, proposals for medical interventions in schools were presented and the dissemination of hygiene notions among the people in the created services for the prophylaxis of the so-called rural endemic diseases was prioritized. Thus, in this context, the education was seen as an important resource to promote a change of habits in the population and the doctors sought in such a way to accomplish a manners reform with the hygiene as a base.